2019
DOI: 10.1111/dom.13681
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of ertugliflozin in Asian patients with type 2 diabetes mellitus inadequately controlled with metformin monotherapy: VERTIS Asia

Abstract: Aim: Phase III, randomized, double-blind study evaluating the efficacy and safety of ertugliflozin in Asian patients with type 2 diabetes mellitus (T2DM) inadequately controlled on metformin, including evaluation in the China subpopulation. Materials and methods:A 26-week, double-blind study of 506 Asian patients (80.2% from mainland China), randomized 1:1:1 to placebo, ertugliflozin 5-or 15 mg, was performed. Primary endpoint was change from baseline in HbA1c at week 26. Secondary endpoints were change from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 24 publications
6
49
0
Order By: Relevance
“…There were no reports of severe hypoglycaemia in the E/SE Asian population. The observed safety profile is consistent with the overall safety data that have been published for ertugliflozin to date …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…There were no reports of severe hypoglycaemia in the E/SE Asian population. The observed safety profile is consistent with the overall safety data that have been published for ertugliflozin to date …”
Section: Discussionsupporting
confidence: 89%
“…The efficacy findings are also consistent with those reported in a meta- profile is consistent with the overall safety data that have been published for ertugliflozin to date. 9,[11][12][13][14][15]25 East/SE Asian patients included in the current analysis of ertugliflozin efficacy had normal baseline renal function with a baseline eGFR similar to studies of other SGLT2 inhibitors in Asian and E/SE Asian populations (85.9 to 95.3 mL/min/m 2 ). 19,20 A small initial decrease from baseline in eGFR was observed with ertugliflozin in the E/SE Asian population in the placebo pool and active-comparator study that returned to baseline over time.…”
Section: Safetymentioning
confidence: 83%
“…The PK findings reported here in Chinese subjects residing in China are comparable with those observed in other populations and are supported by results from a recently conducted phase 3 study exploring the efficacy and safety of ertugliflozin in Asian patients with T2DM . This longer‐term study (with the same ertugliflozin doses of 5 mg and 15 mg assessed in the current phase 1 study) demonstrated that ertugliflozin improved glycemic control and reduced body weight and systolic blood pressure in Asian patients with T2DM inadequately controlled on metformin monotherapy, including Chinese patients from mainland China . Taken together, the comparable efficacy and safety across the ertugliflozin phase 3 studies in varied populations including Chinese patients and the PK findings from the phase 1 studies suggest no clinically meaningful PK differences, and no dose modification of ertugliflozin is required based on race or body weight.…”
Section: Discussionsupporting
confidence: 86%
“…Of the 22 089 hits retrieved from our search, 144 studies met our inclusion criteria (Figure ). An agreement value ( κ ) of 80% was achieved for studies requiring detailed analysis and extraction.…”
Section: Resultsmentioning
confidence: 99%